Pelvic examination may be meaningfully taught to novices and be used to predict operating times for laparoscopic excision of endometriosis in one surgical procedure. (23rd November 2017) - Bhatti, Mominah; Ketheeswaran, Ashradha; Arnold, Amy; Nesbitt‐Hawes, Erin; Deans, Rebecca; Won, HaRyun; Abbott, Jason
Abstract : Objective: To investigate whether pelvic examination may be meaningfully taught to novice medical students and its accuracy in predicting operating times for laparoscopic excision of endometriosis at a single surgical procedure. Methods: Women with suspected endometriosis scheduled for laparoscopy underwent pelvic examination to estimate operative time by medical students (novices), trainees, senior clinicians with <10 years surgical experience (experts) and ≥10 years (masters). Examination and intraoperative findings were compared and stage of disease recorded. Results: There were 138 estimations of operating time at the initial assessment and 251 estimations of operating time prior to surgery. The median surgical duration was 44 min (range 12–398) and increased progressively with revised American Society for Reproductive Medicine disease stage. Clinical predictions exceeded actual operating times by a median of 18 min (range overestimating by 180 min and underestimating by 120 min) with 80% of procedures completed in less time than predicted and none requiring a second procedure. There was no statistical difference in operative time estimations between the groups with students and trainees underestimating surgical duration by a median of two and five minutes, respectively, experts having a median time difference of zero minutes, and masters overestimating by 4.5 min. Conclusion: Targeted pelvic examining may be taught to novices (medical students) and can be used to predict operating time at one surgical procedure. Less experienced examiners have a tendency to underestimate surgical duration, with masters overestimating surgical time when scheduling laparoscopies for endometriosis, and increasing disease stage is associated with a less precise estimation of surgical duration.